In Vitro Susceptibilities of Neisseria gonorrhoeae to Fatty Acids and Monoglycerides - Bergsson, Gudmundur (American Society for Microbiology, 1999)
The susceptibility of Neisseria gonorrhoeae to several medium-chain fatty acids and their 1-monoglycerides was tested at a short inactivation time of 1 min. The results indicate that monocaprin, a monoglyceride of capric acid (10 carbon atoms, no double bonds), causes the fastest and most effective killing of all strains of N. gonorrhoeae tested.